Adventurers, Flâneurs, and Agitators : Travel Stories as Means for Marking and Transgressing Boundaries in 19th and Early 20th Century Finland - Salmi-Niklander, Kirsti (My University, 2014)
The article focuses on border crossings in travel stories, which were published in hand-written newspapers in 19th- and early 20th-century Finland. These papers were a popular tradition in student organizations and popular movements. Border crossings appear in travel stories in three different representations. Firstly, border crossings are repeated motifs in travel stories, both as challenging events and as small gestures and encounters. Travel stories demarcate boundaries, but they also provide a means for transgressing them. Secondly, hand-written newspapers as a literary practice highlight borders between oral and written communication. They were produced as one single manuscript copy, and published by being read out aloud in social events. Thirdly, the authors of hand-written newspapers were placed on the border of different positions in society such as class, gender and age. My analysis is based on the methodological discussion of small stories and personal experience narratives; travel stories can be defined as “local event narratives”. I have outlined four basic models for travel stories which emerge from hand-written newspapers: the great mission story, the grand tour story, the flâneur story and the retreat story. The analysis of travel stories is presented through four different case studies with a time range from the 1850s to the 1920s: these materials have been produced in two provincial student fraternities (osakunta), in the temperance society “Star” in Helsinki in the 1890s, and in the Social Democratic Youth Club in the small industrial town of Karkkila in the 1910s and the 1920s. Many parallel features can be observed in travel stories, even though the social background and ideology of the authors are quite different. Time and space are important aspects in travel stories, and they often demarcate boundaries of class and gender.
Keywords: 306 Kultur und Institutionen; travel stories; hand-written newspapers; border crossings; class; gender; oral-literary tradition; narration